Automating Data Pipelines with AI for Scalable, Real-Time Process Optimization in the Cloud - Srinivas Kolluri (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Modern data processing environments demand efficient, scalable solutions for handling massive data streams in real-time, yet traditional Extract, Transform, Load (ETL) pipelines face significant limitations in processing speed and adaptability. This article presents an AI-Enhanced Cloud Data Pipeline (AECDP) framework that combines Deep Learning-based Stream Processing (DLSP) with Adaptive Resource Management (ARM) for real-time data optimization. The framework introduces novel algorithms for stream processing, resource allocation, and quality assurance, including the Adaptive Stream Processing Algorithm (ASPA) and Anomaly Detection and Correction (ADC) system. The implementation utilizes a multi-cloud architecture with containerized microservices, enabling independent scaling and maintenance of pipeline components. Experimental results demonstrate the framework’s effectiveness across various industry applications, including e-commerce, financial services, and manufacturing sectors. The system achieves consistent sub-second latency for real-time processing, linear throughput scaling, and optimal resource utilization across cloud instances. Additionally, the framework incorporates advanced security features and automated quality monitoring systems, ensuring robust and reliable data processing. The AECDP framework represents a significant advancement in data pipeline automation, providing organizations with a comprehensive solution for managing complex data processing requirements while maintaining high performance and reliability standards.